The Relationship Of Work Motivation And Stress Management With Teacher's Affective Commitment At Country Senior High School Country 1 Datuk Bandar Tanjungbalai City District - Muhammad Rifa'i, Willi Sahana (International Journal Of Education, Social Studies, And Management (IJESSM), 2021)
This study was conducted to see the relationship between Work Motivation and Stress Management with Teacher's Affective Commitment. as for the research method used is a quantitative research method. Quantitative research method is a research method based on the philosophy of positivism. The results of the study are that there is a significant relationship between work motivation and the affective commitment of teachers in SMA Negeri in Datuk Bandar Subdistrict, Tanjungbalai City, there is a significant relationship between stress management and affective commitment of teachers in SMA Negeri in Datuk Bandar Subdistrict, Tanjungbalai City, and there is a positive relationship significant work motivation and stress management with teacher affective commitment. From the multiple correlation analysis, the simultaneous correlation coefficient (R) = 0.911, this value indicates that the relationship between all independent variables and the dependent variable is very strong. In addition, information can also be obtained on how the coefficient of determination is (0.911) x 100% = 91.1%. This value shows that the contribution of all independent variables to the dependent variable simultaneously is 91.1%, while the remaining 8.9% is the contribution of other factors outside this study.